COMPARISON BETWEEN THE BINA MARGA METHOD AND THE 1986 AASHTO METHOD FOR FLEXIBLE PAVEMENT - Ghofar Ismail (NIM 26989016), Achmad
ABSTRACT: The formula used in the Bina Marga Method for flexible pavement design were derived from the 1972 AASHTO method, with some modifications to certain factors, namely Regional Factor and Soil Support. The 1972 AASHTO method was revised and reissued in 1986 as the 1986 AASHTO method. Some new additional factors, for instance Reliability Factor, Subgrade Resilient Modulus, Coefficient of Drainage, Standard Deviation, Moduli of Pavement Material and Environmental Factors, were introduced. The purpose of this study has been to apply the new 1986 AASHTO version for Indonesian conditions by comparing it with the Bina Marga method. For this correlation factors common to each method have been sought and sensitivity testing carried out on key factors. The results of this.study have indicated that there is correlation between the Regional Factor of the Bina Marga Method and the Reliability Factor of the 1986 AASHTO Method. This correlation is only influenced by the CBR value of subgrade. The value of coefficient of drainage in the Bina Marga Method is one, but varies in the 1986 AASHTO Method. This variation affects the total thickness of pavement needed for a particular situation. Some design curves suitable for Indonesian conditions were derived based on the 1986 AASHTO method, and were examined using some specific field data. Results of designing with the 1986 AASHTO method were compared with those found from using the Bina Marga approach. While the former gave greater pavement thickness requirements, the difference was not very significant , which could be attributed to the similarity of subgrade conditions for each of the three project roads examined. Differences could be expected to be wider for different subgrade and environmental conditions.